Численное моделирование электронно-лучевой очистки дымовых газов. Система N₂-O₂-NO - Моргунов, В. В. (НТУ "ХПИ", 2012)
На основі розробленого авторами програмного комплексу "ELO" розрахована ступінь видалення NO в діапазоні від 0 до 50 кГр для суміші газів N₂-O₂-NO. Одержано залежність внеску реакцій в ступінь видалення і освіти наступних хімічних речовин: NO, NO₂, N, O, NO₃, N₂O.

On the base of the software developed by authors the efficiency of NO removal from N₂-O₂-NO system was simulated in the dose range 0 – 50 kGy. The dependencies of formation and sink of following species: NO, NO₂, N, O, NO₃, N₂O by various reactions were received.
Numerical simulation of flue gas treatment under electron-beam purification. N₂-O₂-NO system
Keywords: дымовые газы; очистка газов; электронно-лучевая очистка; программный комплекс "ELO"